Fathers and sons the rise and fall of political dynasty in the Middle East - McMillan, M. E (Plagrave MacMillan, 2013)
In December 2010, a revolution began in Tunisia that rocked the Arab world and ripped up the political rulebook of the Middle East. For generations, power in the Arab world has been monopolized by monarchs or military men. The idea of dynastic power had become so deeply entrenched that, in the twenty-first century, presidents began to act like kings and appoint their sons to succeed them. Yet, this father-to-son transfer of power has absolutely no basis in Islam. To understand how the countries of the Middle East came to be ruled by a system that is distinctly un-Islamic, Fathers and Sons: The Rise and Fall of Political Dynasty in the Middle East traces the history of power in the Arab world from the Prophet to the present and reveals the story behind the headlines of the Arab Spring